2020
DOI: 10.1111/adb.12954
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional sex‐dependent regulation of α6 and β3 nicotinic acetylcholine receptors by protein kinase Cε

Abstract: Nicotine and alcohol are the most commonly abused substances worldwide and are frequently coabused. Nicotinic acetylcholine receptors (nAChRs) containing the α6 and β3 subunits are expressed in neural reward circuits and are critical for nicotine and alcohol reward. nAChRs are dynamically regulated by signaling molecules such as protein kinase C epsilon (PKCε), which impact transcription of α6 and β3 subunit mRNA (Chrna6 and Chrnb3, respectively). Previous work found decreased expression of Chrna6 and Chrnb3 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Furthermore, the PKCε knockout mice had lower expression levels of α6 and β3 nAChR subunit transcripts in ventral midbrain and striatum compared with wild-type mice (Lee & Messing, 2011). Most recently, it was shown that female PKCε knockout mice exhibit higher levels of α6 and β3 nAChR subunit transcripts in ventral midbrain, and show increased sensitivity to the locomotor stimulating effects of nicotine compared to female wild-type and male PKCε knockout mice (Moen et al, 2020). Furthermore, female PKCε knockout mice consumed more nicotine during the first week of access in a twobottle choice procedure than wild-type mice (Moen et al, 2020).…”
Section: Mechanis Ms Of N Achr De S Ens Itiz Ation and Up-reg Ul Ation And Their Role In Withdr Awalmentioning
confidence: 99%
“…Furthermore, the PKCε knockout mice had lower expression levels of α6 and β3 nAChR subunit transcripts in ventral midbrain and striatum compared with wild-type mice (Lee & Messing, 2011). Most recently, it was shown that female PKCε knockout mice exhibit higher levels of α6 and β3 nAChR subunit transcripts in ventral midbrain, and show increased sensitivity to the locomotor stimulating effects of nicotine compared to female wild-type and male PKCε knockout mice (Moen et al, 2020). Furthermore, female PKCε knockout mice consumed more nicotine during the first week of access in a twobottle choice procedure than wild-type mice (Moen et al, 2020).…”
Section: Mechanis Ms Of N Achr De S Ens Itiz Ation and Up-reg Ul Ation And Their Role In Withdr Awalmentioning
confidence: 99%
“…As α6 * nAChRs in the ventral midbrain impact the addictive properties of both alcohol and nicotine, an effect of sex in their regulatory mechanism has important implications for drug development. Notably, we did not observe a sex difference in transcript expression levels of α6, β3, or PKCε itself in PKCε WT animals (Moen et al, 2021). It is possible that the regulation of α6 and β3 nAChR transcripts occurs through distinct PKCε-medicated mechanisms in male and female animals that arise following sexual differentiation of the brain.…”
Section: Baseline Nicotinic Acetylcholine Receptor Expressionmentioning
confidence: 55%
“…One candidate regulatory mechanism involves signaling by protein kinase C epsilon (PKCε), as our group has previously shown that genetic ablation of PKCε results in decreased α6 and β3 nAChR mRNA expression in male mice ( Lee and Messing, 2011 ). However, further characterization of female mice revealed an oppositional effect of sex, with female PKCε knockout animals showing a threefold increase in α6 and β3 transcript expression in the ventral midbrain compared with WT littermates ( Moen et al, 2021 ). Our data also showed a strong correlation between α6 and β3 transcript expression levels in the ventral midbrain across both WT and KO animals, further suggesting shared transcriptional mechanisms involving the CHRNB3-CHRNA6 gene cluster.…”
Section: Sex Differences In Nicotinic Acetylcholine Receptor Expression and Regulationmentioning
confidence: 99%
See 2 more Smart Citations